An ethical framework for global vaccine allocation: The Fair Priority Model offers a practical way to fulfill pledges to distribute vaccines fairly and equitably - Emanuel, Ezekiel J. (2020)
Once effective coronavirus disease 2019 (COVID-19) vaccines are developed, they will be scarce. This presents the question of how to distribute them fairly across countries. Vaccine allocation among countries raises complex and controversial issues involving public opinion, diplomacy, economics, public health, and other considerations. Nevertheless, many national leaders, international organizations, and vaccine producers recognize that one central factor in this decision-making is ethics (1, 2). Yet little progress has been made toward delineating what constitutes fair international distribution of vaccine. Many have endorsed ?equitable distribution of COVID-19?vaccine? without describing a framework or recommendations (3, 4). Two substantive proposals for the international allocation of a COVID-19 vaccine have been advanced, but are seriously flawed. We offer a more ethically defensible and practical proposal for the fair distribution of COVID-19 vaccine: the Fair Priority Model.The Fair Priority Model is primarily addressed to three groups. One is the COVAX facility?led by Gavi, the World Health Organization (WHO), and the Coalition for Epidemic Preparedness Innovations (CEPI)?which intends to purchase vaccines for fair distribution across countries (5). A second group is vaccine producers. Thankfully, many producers have publicly committed to a ?broad and equitable? international distribution of vaccine (2). The last group is national governments, some of whom have also publicly committed to a fair distribution (1).These groups need a clear framework for reconciling competing values, one that they and others will rightly accept as ethical and not just as an assertion of power. The Fair Priority Model specifies what a fair distribution of vaccines entails, giving content to their commitments. Moreover, acceptance of this common ethical framework will reduce duplication and waste, easing efforts at a fair distribution. That, in turn, will enhance producers' confidence that vaccines will be fairly allocated to benefit people, thereby motivating an increase in vaccine supply for international distribution.